Impact of solvent on the solution-processed hole transport layer deposition in organic solar cells - Neeraj Chaudhary; Rashi Kedia; Manisha Khatak; Manisha Balkhandia; Asit Patra (Next Materials)
Recently, the solution-processed copper[I] iodide (CuI) thin film deposition has been identified as an important hole transport layer (HTL) in excitonic solar cells. Further, we explored the potential of CuI as an efficient HTL and introduced a range of solvents compatible with CuI for the preparation of organic solar cells. This work investigates the impact of various solvent on physical properties of CuI. Eight solvents namely; cyclohexane, carbon tetrachloride (CCl4), benzene, tetrahydrofuran, dichloromethane, acetonitrile, dimethoxy sulfoxide (DMSO) and water (H2O) were selected for density functional calculations and for that purpose we used the basis set B3LYP/3-21 g to access the impact of solvents on energy levels, charge distribution and atomic distance within CuI. Based on the computational results, hydrophilic organic solvents DMSO along with N,N-dimethylformamide (DMF), and diisopropyl sulphide (DPS) were chosen to dissolve CuI for the solution-processed HTL. The HTL formed from these three solvents were analysed using UV–vis–NIR spectroscopy, cyclic voltammetry, X-ray diffraction and scanning electron microscope (SEM) to get the better understanding of their electrical, optical and morphological behaviour. To evaluate the effectiveness of this HTL material employing different solvents, two active layers PTB7:PC71BM and PCDTBT:PC71BM were tested with the device configuration ITO/CuI/active layer/Al. Our results indicate that the choice of solvent for the HTL deposition significantly influence the photovoltaic performance with DMSO as a solvent achieving the highest power conversion efficiency (PCE) of ̴ 4.28 % in this particular case for CuI which is due to the more crystalline film yielded with DMSO under ambient conditions.